2020
DOI: 10.1021/acs.jchemed.0c00772
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Communication in the Success/Failure of Remote Learning of Chemistry during COVID-19

Abstract: Owing to the COVID-19 global pandemic, three chemistry instructors at Ferris State University, with no previous online instructional experience, made the abrupt midsemester switch from face-to-face to remote delivery in their respective chemistry courses. This paper discusses the importance of communication during the rapid change to remote delivery, the factors affecting the quality of remote delivery communication, and the students' experience based on surveys given at the end of the 8 weeks online. The imme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…The higher flexibility of the asynchronous delivery model was also noted as a significant benefit by students experiencing the Spring 2020 transition to remote learning. 19,20,22,32,34,35,37,40,42,53,54 Another significant benefit of asynchronous lecture delivery, as noted by the students, and also seen within recent literature, was the greater level of control it provided over the learning experience. 7,19,20,22,23,35,38,41,42,52 Specifically, students highlighted the ability to pause and rewind the lecture videos.…”
Section: Asynchronous Vs Synchronous Deliverymentioning
confidence: 84%
“…The higher flexibility of the asynchronous delivery model was also noted as a significant benefit by students experiencing the Spring 2020 transition to remote learning. 19,20,22,32,34,35,37,40,42,53,54 Another significant benefit of asynchronous lecture delivery, as noted by the students, and also seen within recent literature, was the greater level of control it provided over the learning experience. 7,19,20,22,23,35,38,41,42,52 Specifically, students highlighted the ability to pause and rewind the lecture videos.…”
Section: Asynchronous Vs Synchronous Deliverymentioning
confidence: 84%
“…Each teacher described instances where either they or a colleague had students enrolled in their class that simply did not respond at all. Communication with students has been identified as a crucial factor that influences the success of online learning (Garbe et al, 2020;Kollalpitiya et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that students prefer recorded lectures to be broken into minilectures is corroborated by a number of other studies. Reports by both McCusker & Mohseni (2020) and Kollalpitiya (2020) suggested that students were unable to maintain attention during long recorded lectures. Sarju (2020) adopted shorter recordings to support the management of cognitive load, and found that these were valued by student, who viewed them in preference to full lecture recordings from a previous year that were also provided.…”
Section: Implications For Practicementioning
confidence: 99%